Roadkills as a Method to Monitor Raccoon Dog Populations - Linas Balčiauskas (MDPI AG, 2021)
The raccoon dog (Nyctereutes procyonoides) is one of the most frequently killed species on Lithuanian roads. As an invasive species, up-to-date knowledge of population size, trends and spatial distribution is critically important both for species assessment and for the planning of control measures. In Lithuania, however, raccoon dog surveys have not been carried out since 1997. We investigated, therefore, whether roadkill counts on predefined routes could be used as a proxy for a survey. Our dataset includes survey numbers for the period 1956–1997, hunting bag sizes for 1965–2020 (including the spatial distribution of the hunting bag in 2018–2020) and roadkill data relating to 1551 individuals between 2002–2020. At the most local scale, that of the hunting areas of hunting clubs, correlations between the numbers of hunted and roadkilled individuals were negative and insignificant or absent. At the country scale, however, we found significant correlation both between the numbers surveyed and hunted in 1965–1997 (r = 0.88), and between those hunted and the number of roadkills in 2002–2020 (r = 0.56–0.69). Therefore, we consider that roadkill counts on predefined and stable routes may be used as a proxy for a survey at the country scale. Practical implementation of the method is proposed.